Development, validation and evaluation of nutrition and psychological management module for bariatric surgery patients in Hospital Universiti Sains Malaysia - Majid, Nor Latifah Ab (2024)
Globally escalating obesity rates have increased health risks, prompting bariatric surgery as a final resort for severe and complex obesity. Despite its benefits, bariatric surgery has complications, requiring lifelong dietary and lifestyle changes. Malaysia currently relies on foreign guidelines, highlighting the need for locally tailored guidelines. Therefore, this study aimed to develop and validate a comprehensive nutritional and psychological management module for bariatric surgery to address common issues and guide patients and healthcare professionals. All bariatric patients at Hospital Universiti Sains Malaysia (Hospital USM). This study was conducted from March 2022 to June 2023 and included three phases. Phase one involved the mixed methods approach, combining a quantitative method of 63 participants to identify complications, dietary habits, and psychological status, and a qualitative method of 12 participants to explore the underlying causes of these issues and strategies to address them. The most frequent bariatric surgery was laparoscopic sleeve gastrectomy (71.4%) and the most reported complications were hair loss (50.8%), gastroesophageal reflux disease (GERD) (49.2%) and frequent vomiting (41.3%). There were significant differences in genders reporting dry skin and hair loss, and the mean weight and body mass index (BMI) before and after bariatric surgery (p<0.001). In addition, qualitative findings also highlighted issues with gastric problems, GERD, food intolerance, lethargy, nausea, and vomiting. The mean intake of fibre, vitamin D, vitamin B-1, vitamin B-9, vitamin B-12, vitamin K, potassium, calcium, iron, magnesium, zinc and copper for men and women did not meet the recommendations. Most participants were psychologically healthy and only some reported having severe (3.2%) and extremely severe (6.3%) anxiety. The second phase involved the development of the module and the content and face validation by 11 experts. The value of S-CVI/Ave is 0.98 S-CVI/UA is 0.83 and all S-FVI/Ave scores achieved satisfaction except the S-FVI/UA score for three components were below the acceptable FVI value. The third phase was the evaluation of the module by 30 bariatric patients. Most participants were satisfied with all the components of the module with some suggestions to improve the module such as using more attractive pictures, simpler language and adding more menus. In conclusion, this module achieved the research objectives and can be used in hospitals throughout Malaysia as a nutritional and psychological management guideline benefiting both bariatric patients and healthcare professionals thus, optimizing the success of bariatric procedures.